UNMASKING FINANCIAL SHENANIGANS INDICATION: FRAUD HEPTAGON APPLICATION IN INDONESIA'S HEAVY CONSTRUCTION AND CIVIL ENGINEERING SECTOR - Puspita, Aulia Dewi; Jannah, Richatul (Universitas Bunda Mulia, 2026)
Background: Fraudulent financial statements represent the most financially damaging form of fraud and the construction sector ranks as the highest risk sector globally for this scheme. Alongside, Indonesia currently ranks as the third nation for fraud cases across Asia Pacific, creating an urgent need to examine this phenomenon within its national context. Objective: This study aims to investigate the drivers of fraudulent financial statements through financial shenanigans within Indonesian heavy construction and civil engineering firms using the fraud heptagon framework. Research Methods: This study employs a quantitative panel data analysis method using secondary financial data from 13 publicly listed companies (2017-2023), selected with purposive sampling, and analyzed with fixed effect regression models. Research Results: he findings reveal that intense financial target pressures and high employee turnover significantly elevate fraud risk. In contrast, external pressures from financial leverage demonstrates a counterintuitive mitigating effect. Furthermore, most conventional fraud triggers show no statistically significant influence. Originality/Novelty of Research : This research contributes to the literature by integrating financial shenanigans analysis within the Fraud Heptagon framework, especially allowing the use of the religiosity variable while still considering the integrity variable.